2007
DOI: 10.1038/sj.onc.1210835
|View full text |Cite
|
Sign up to set email alerts
|

PAX-FKHR function as pangenes by simultaneously inducing and inhibiting myogenesis

Abstract: Alveolar rhabdomyosarcomas (ARMS) escape terminal differentiation despite exhibiting a skeletal muscle phenotype. To understand the role of the ARMS-specific PAX-FKHR proteins in myogenesis, we characterized their regulation of MyoD expression and function. Reporter assays show that PAX-FKHR transactivate MyoD expression through its 258 bp core enhancer. Gel-shift assays confirm that PAX-FKHR bind to core enhancer sequences showing similarity to consensus PAX3/PAX-FKHRbinding sites. We show that while PAX3-FKH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…On the other hand, the transience of PAX3-FOXO1 RNA is consistent with the normal process of muscle differentiation, as prolonged production of PAX3-FOXO1 RNA leads to constant expression of MYOD and MYOG , which then blocks terminal differentiation ( 13,14 ). We reasoned that a posttranscriptional process, such as trans -splicing of precursor mRNAs, can give rise to transient, temporal appearance of the fusion product ( 16,17 ), whereas gene fusions caused by chromosomal translocation result in constitutive synthesis of chimeric PAX3-FOXO1 RNA, and in turn MYOD and MYOG expression that permanently arrests myocytes at immature forms, which can potentially lead to ARMS if combined with secondary mutations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, the transience of PAX3-FOXO1 RNA is consistent with the normal process of muscle differentiation, as prolonged production of PAX3-FOXO1 RNA leads to constant expression of MYOD and MYOG , which then blocks terminal differentiation ( 13,14 ). We reasoned that a posttranscriptional process, such as trans -splicing of precursor mRNAs, can give rise to transient, temporal appearance of the fusion product ( 16,17 ), whereas gene fusions caused by chromosomal translocation result in constitutive synthesis of chimeric PAX3-FOXO1 RNA, and in turn MYOD and MYOG expression that permanently arrests myocytes at immature forms, which can potentially lead to ARMS if combined with secondary mutations.…”
Section: Discussionmentioning
confidence: 84%
“…Studies in fi broblast and rhabdomyosarcoma cell lines have demonstrated that the PAX3-FOXO1 protein simultaneously induces myogenesis while blocking differentiation to mature muscle, thereby contributing to the formation of ARMS ( 13,14 ). To test the effect of constant expression of PAX3-FOXO1 in the muscle differentiation setting, MSC cells were infected with retroviral vectors that overexpress PAX3-FOXO1 ( Fig.…”
Section: Research Articlementioning
confidence: 99%
“…A typical feature of ARMS also includes the myogenic phenotype with expression of MyoD, 14 a bona fide target of PAX3-FKHR, 13,15 which acts as a key regulator of myogenic gene expression, leading to terminal differentiation. 16 However, they fail to complete the terminal myogenic differentiation program.…”
Section: Akt and Pax3-fkhr Cooperation Enforces Myogenic Differentiatmentioning
confidence: 99%
“…Pax3-Foxo1 orchestrates the expression of numerous Pax3 downstream genes with increased amplitude and without feedback control, impairing the apoptosis and differentiation processes [49][50][51][52][53] and conferring a G2 checkpoint-dependent resistance to irradiation in vitro and in vivo. 54 For example, the Pax3-Foxo1-dependent transcription of genes like hepatocyte growth factor receptor (HGFR or c-MET), FGFR4, IGF-2 and C-X-C chemokine receptor type 4 (CXCR4) contributes to increase tumor aggressiveness and metastasis recurrence.…”
Section: Pax3-foxo1 Oncoproteinmentioning
confidence: 99%